Documentation Bulletin No. 2 - Planning Commission (Planning Commission, 1965)
Considering the urgent need felt the Fourth Plan working group on Implementation etc. of agricultural programmes, the Ministry of Food and Agriculture suggested that the Programme Evaluation Organisation might undertake an early study of the problems besetting the coordinated implementation of agricultural programmes. It is in this background that the P.E.O. took up in 1964 type study of the main bottlenecks and difficulties faced in the implementation of agricultural programmes at the district and block levels.
Programme Evaluation Organisation Planning Commission Government of India